MODEL PENGEMBANGAN AGROWISATA DALAM RANGKA PEMBERDAYAAN KELOMPOK TANI TAWANGREJO ASRI - Arifin, Miftakhul; Sulastiyah, Amie; Yekti, Ananti; Wartapa, Agus (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
This study aimed to understanding the agroecosystem of Tawangrejo subvillage, condition it that is analyzed by SWOT, and to find the development model of the agribusiness tour. It was qualitative in nature. The data were collected through interview and observation methods, and analyzed using the qualitative descriptive. The result of the study is as the followings. The agroecosystem of Tawangrejo subvillage has generally prospect to contributing the agribusiness tour. The result of SWOT analysis is showed that has very aspects to contributing the agribusiness tour. The development of the agribusiness tour can be used through development of physical, institusional, technical, economical, cultural and artistical conditions.